Introducing and Clarifying the Ideas Makes Team Work Successful - Cheng Pei Jung (Mathematical Statistician and Engineering Applications, 2023)
To examine the development of design teams’ ideation using the IDEATOR design supporting tool, five design teams were invited to conduct a design task. The verbal communication data and idea sketches of the five design teams were explored and analyzed by researcher and three coders. The research results revealed that the frequent verbal communication of team members expounding their ideas and spontaneously proposing concepts contributed to the lateral-thinking development reflected in the sketches. However, their frequent verbal communication inviting other members to propose ideas or decisions had a negative effect on said thinking development.